The efficacy and safety of anti-PD-1/PD-L1 in treatment of glioma: a single-arm meta-analysis - Zeng, Yi-Fan; Wei, Xin-Yu; Guo, Qi-Hao; Chen, Si-Yu; Deng, Sheng; Liu, Zheng-Zheng; Gong, Zhi-Cheng; Zeng, Wen-Jing (Frontiers in Immunology, 2023)
Objective: This meta-analysis aimed to evaluate the efficacy and safety of PD-1/PD-L1 inhibitors in patients with glioma. Methods: PubMed, EMBASE, Web of Science, and the Cochrane library were searched from inception to January 2023 without language restriction. Primary outcomes include overall survival (OS), progression-free survival (PFS), objective response rate (ORR), and adverse events (AEs). The risk of bias evaluation was assessed by subgroup analysis, sensitivity analysis, and publication bias, including funnel plot, Egger’s test, and Begg’s test. Results: A total of 20 studies involving 2,321 patients were included in this meta-analysis. In the analysis of phase III clinical trials included, the forest plot showed that PD-1/PD-L1 inhibitor could not improve the OS (HR=1.15, 95% CI: 1.03-1.29, P=0.02, I2=14%) and PFS (HR=1.43, 95% CI: 1.03-1.99, P=0.03, I2=87%). In the single-arm analysis, the forest plot demonstrated that the 6-month OS was 71% (95% CI: 57%-83%, I2=92%), 1-year OS was 43% (95% CI: 33%-54%, I2 = 93%), and the 2-year OS was 27% (95% CI: 13%-44%, I2=97%). The pooled estimate of the median OS was 8.85 months (95% CI: 7.33-10.36, I2=91%). Furthermore, the result indicated that the 6-month PFS was 28% (95% CI: 18%-40%, I2=95%), 1-year PFS was 15% (95% CI: 8%-23%, I2 = 92%), and the 18-month PFS was 10% (95% CI: 3%-20%, I2=93%). The pooled estimate of the median PFS was 3.72 months (95% CI: 2.44-5.00, I2=99%). For ORR, the pooled estimate of ORR was 10% (95% CI: 2%-20%, I2 = 88%). We further analyzed the incidence of PD-1/PD-L1 inhibitor-related AEs, the pooled incidence of AEs was 70% (95% CI: 58%-81%, I2=94%). The incidence of AEs ≥ grade 3 was 19% (95% CI: 11%-30%, I2=94%). The funnel plot for the median PFS and median OS was symmetric without significant differences in Egger’s test and Begg’s test. The sensitive analysis revealed that our results were stable and reliable. Conclusion: The results of this meta-analysis suggest that anti-PD-1/PD-L1 therapy is relatively safe but could not prolong survival in glioma. More randomized controlled trials are needed to confirm our results.